PENGARUH MODEL PEMBELAJARAN KOOPERATIF NUMBERED HEAD TOGETHER (NHT) DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI HAK DAN KEWAJIBAN DI UPT SD NEGERI 107 GRESIK - Mega Arlisyah Giri Indrati; Ulhaq Zuhdi; Kasiani Kasiani (CV. ADIBA AISHA AMIRA, 2023)
This research is motivated by the low learning outcomes of students in the matter of rights and obligations. The low learning outcomes are due to a lack of interest in material rights and obligations, lack of concentration and discussion during learning. The goal to be achieved in this study is to determine the effect of the Numbered Head Together (NHT) cooperative learning model in improving student learning outcomes on the subject of rights and obligations at UPT SD Negeri 107 Gresik. This type of research, namely Classroom Action Research (CAR), was carried out using two cycles. The implementation of the cycle uses 4 stages, namely planning, implementing, observing, and reflecting. The research subjects were 8 grade IV students at UPT SD Negeri 107 Gresik. The data collection method used is the test. Panelitian using pretest and posttest. Data analysis techniques used the normality test, homogeneity test and t-test using the SPSS version 25 application. The results showed that the pretest average value was 81.875. In the first cycle the posttest average score was 83.75 and the second cycle had a posttest average score of 95. The posttest score was higher than the pretest score so there was an increase in learning outcomes. The T-Test using the SPSS version 25 application shows that the t-test results obtained, namely the Sig (2-tailed) value is (0.000) so that a value less than (0.05) explains that there is a significant difference between the results of the pretest and posttest. From this explanation, it can be concluded that there is an influence of the Numbered Head Together (NHT) cooperative learning model in improving student learning outcomes on the material rights and obligations at UPT SD Negeri 107 Gresik.